Enhancing Students’ Mathematical Representation and Learning Motivation through Problem-Based Learning Worksheets in the Sound Wave Topic - Watuna, Monica Ananda; Dwandaru, Wipsar Sunu Brams; Nasir, Muhammad Hilmi; Wiyatmo, Yusman (Jurnal Pendidikan MIPA, 2025)
This study aims to examine the implementation of student worksheets based on the problem-based learning model to enhance students’ mathematical representation skills and learning motivation in the topic of sound waves. Problem-based learning (PBL) makes the study of sound waves more engaging for students by emphasizing the comprehension of ideas and their application in the real world, rather than memorizing formulas. The research was conducted in Class XI of SMA Negeri 1 Godean, Yogyakarta, involving 33 students, using a quantitative approach and a pre-experimental design in the form of a one-group pretest-posttest design. The instruments used were a mathematical representation ability test and a learning motivation questionnaire. The data analysis results showed an increase in the average post-test scores compared to the pre-test. Based on the paired sample t-test, students' mathematical representation skills showed a statistically significant improvement (p < 0.001) with an N-gain score of 0.68, resulting in an increase in scores from 51 to 85. This result is supported by the effectiveness test using Cohen's d, which indicated a very large effect size (d = 2.35). Meanwhile, students' learning motivation showed a statistically non-significant increase (sig. = 0.055 > 0.05), with an N-gain score of 0.038 and a slight increase in scores from 48 to 50. Cohen's d effect size test for learning motivation fell into the small effect category (d = 0.32). Although not statistically significant, there was an indication of improved student learning outcomes after the intervention, as reflected in the mean score differences. These results show that problem-based learning models integrated into student worksheets are highly effective in enhancing students' mathematical representation abilities and raising their motivation to learn. Therefore, the implementation of problem-based learning student worksheets can serve as an effective alternative instructional strategy in physics education, particularly in improving students' cognitive aspects. Further research with a more extended implementation period and a more comprehensive approach is recommended to optimize the impact on affective aspects.   Keywords: problem-based learning, student worksheet, mathematical representation, learning motivation, sound waves.